Upaya Peningkatan Kapasitas Produksi & Koeifisien Efisiensi Improvement di Proses K-Contactor Backend pada PT X - Alexander Alfredo; Siana Halim (Jurnal Titra, 2023)
PT X is a company engaged in the electrical sector. This research was conducted to increase production capacity due to a surge in demand of 8% from the previous year for K-Contactor products. PT X has an average production of 342 contactors per hour and has been unable to meet the new K-Contactor production target. PT X wants to increase production capacity by 375 pcs per hour. The new target was given to meet the surge in demand. Then the company also wants to improve the Coefficient Efficiency rate towards 80%, which is currently still between 65-75%, which will automatically increase if the production target is reached, then the Coefficient Efficiency rate will automatically increase.